Sintering behaviour and properties of manganese-doped alumina - Dhuban, S.B.; Ramesh, S.; Tan, C.Y.; Wong, Y.H.; Alengaram, U.J.; Subathini, R.; Teng, W.D.; Tarlochan, F.; Sutharsini, U. (University of Jaffna, 2019)
The effect of manganese (0.1, 0.5 and 1.0 wt%) on the sintering and mechanical properties of alumina was studied. Sintering was carried out by the conventional heating method in a box furnace and in a hybrid mul timode microwave furnace. XRD analysis revealed the precipitation of a spinel second phase (MnAl2O4) in manganese-doped samples as a result of manganese limited solubility in the corundum lattice. The addition of 0.1 wt% manganese was most beneficial in enhancing the densification of alumina (97.5% relative density when compared to 94.2% for the undoped sample), hindered grain growth, and improved the hardness of the ceramic when sintered at 1500 °C. The study also revealed that microwave sintering was effective in suppressing grain growth of alumina. In addition, the hardness was dependent on the sintered bulk density and that grain coar sening ensued as the density of the sintered alumina exceeded 95% of theoretical.
Keywords: Alumina; sintering additive; manganese doping; microwave sintering; conventional sintering